Facultative Labour Arbitration as Final Offer Arbitration - Velásquez Meléndez, Raffo (2015)
This article explains how it was formed and shaped the Facultative Labour Arbitration optional by the judgments of the Constitutional Court, in order to that the workers or the employer may resort and request the initiation of arbitration which their counterpart must be submitted obligatorily, without previous arbitration clause or agreement. the constitutional system requires that the labor arbitration has to be an alternative mechanism to the negative response of the previous negotiations.